A Survey on the Effectiveness of Existing Smart Home Cyber Attacks Detection Solution: A Broadband Service Providers’ Perspective - Md Mizanur Rahman; Faycal Bouhafs; Frank den Hartog (IEEE Open Journal of the Communications Society)
The Internet of Things (IoT) is rapidly reshaping smart homes with innovative technologies for everyday convenience. Although smart home technologies are becoming more popular, many homeowners lack the expertise and skills to operate them. Particularly mismanaged networking technologies often result in homeowners complaining to their Broadband Service Providers (BSPs) when there are disruptions to the performance of the smart home devices and services. Current remote management solutions used by BSPs offer limited functionality and accuracy in identifying the causes of these disruptions. Causes may include legitimate factors, such as misconfiguration, interference, and congestion, but they could also be the result of cyber attacks. This review exposes knowledge gaps that impede the development of effective troubleshooting tools (particularly related to cyber attacks) for BSPs, including network-related challenges and dataset limitations. We also discuss future research directions, emphasising scalable and data-efficient methods to reduce storage requirements, costs, and privacy concerns, which will enable BSPs to manage millions of customer networks more effectively.